2018
DOI: 10.3390/ani8020026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Cognition and Range Use in Free-Range Laying Hens

Abstract: Simple SummaryIndividual free-range laying hens vary in their use of the outdoor range. The outdoor environment is typically more complex and variable than indoor housing and thus range use may be related to differences in spatial abilities. Individual adult hens that never went outside were slower to learn a T-maze task—which requires birds to repeatedly find a food reward in one arm of the maze, compared to outdoor-preferring hens. Pullets that were faster to learn the maze also showed more visits to the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
(47 reference statements)
2
37
1
Order By: Relevance
“…In this study, we tested whether and how differences in the ranging behaviour of free-range chickens affect motor self-regulation performance during a cylinder task. The recent literature on free-range chickens and junglefowl has confirmed the influences of animal personality on cognition [18,19]. We recently showed that differences in ranging behaviour in free-range chickens were stable across time (indicative of a personality trait) and influenced spatial memory performances, with less exploratory chickens showing better spatial memory when compared to high exploratory ones [20].…”
Section: Introductionmentioning
confidence: 83%
“…In this study, we tested whether and how differences in the ranging behaviour of free-range chickens affect motor self-regulation performance during a cylinder task. The recent literature on free-range chickens and junglefowl has confirmed the influences of animal personality on cognition [18,19]. We recently showed that differences in ranging behaviour in free-range chickens were stable across time (indicative of a personality trait) and influenced spatial memory performances, with less exploratory chickens showing better spatial memory when compared to high exploratory ones [20].…”
Section: Introductionmentioning
confidence: 83%
“…The typical motionless response of laying hens in novel environments highlights a confound with individual behavioural assessments that requires movement to execute the test. Previous measurements of cognitive and learning abilities that require bird training have excluded hens that do not make training criterion due to lack of movement (Campbell et al, 2018;Krause et al, 2006;Nordquist et al, 2011). Similarly, previous tests of judgement bias have shown fearful hens were less flexible during task learning than non-fearful hens (fearfulness was assessed in an open field test; de Haas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an RFID system based on ultra-wideband technology was developed for monitoring 42 individual chickens' locations in the 100 m × 100 m experimental field, which could calculate the position with 0.29 m of the median error and 68% of the registration rate (Stadig et al, 2018a). Monitoring of outdoor range use at the individual level allows for correlation between ranging and welfare indicators such as tonic immobility test, plumage damage, foot health and spatial cognition (Campbell et al, 2016(Campbell et al, , 2018a(Campbell et al, and 2018bHartcher et al, 2016;Larsen et al, 2018;Taylor et al, 2018).…”
Section: Tracking Movement and Feeding Behaviour Of Individualsmentioning
confidence: 99%